Practice and managment of investment in Nigeria : an instructional manual for banking and finance students - Fadeyi, Lawrence Akinkunle (Lagos, Nigeria : Asla Publishers, 1992)
Aimed at making it easy for the banking and finance students, business executives, accountants and non-accountants who are seeking to come to terms with the world of investment with a view to acquiring a thorough working knowledge of investment decisions.
Includes index.
oif 26/02/15
Loan
Keywords: Investments -- Nigeria